Addictovigilance contribution during COVID-19 epidemic and lockdown in France - Lapeyre-Mestre, Maryse (Therapie, 2020)
Addictovigilance is a safety monitoring targeted at substances with potential for abuse and dependence. This vigilance was involved during the period of COVID-19 epidemic due to the significant changes in access to drugs and psychological disruption caused by the pandemic and lockdown. This article aims to present the different steps implemented by the French Addictovigilance network in collaboration with the French Health authorities from March to May 2020, including monitoring of potential harmful events, and scientific communication. The first events were identified through the continuity of the networking between the French addictovigilance centres and their partners: community pharmacies, general practitioners, specialized structures and emergency wards. As soon as the lockdown began, first cases of overdoses (lethal or not) were reported with opioids, mainly with methadone, and other opioids (heroin, oxycodone, tramadol or antitussive codeine). Lockdown-related noteworthy events consisted in clinical cases or other relevant information for which lockdown clearly played an important role: among the many substances identified at least once, pregabalin, benzodiazepines, cannabis, cocaine and nitrous oxide were the most significant in terms of prevalence, seriousness or particularly specific to the lockdown context. Despite significant decrease in the activity and travel limited to vital needs, community pharmacies continued to identify falsified prescriptions in this period, highlighting an increase in suspicious requests for pregabalin, codeine and tramadol. In parallel, the French addictovigilance network continued its communications efforts in the period, issuing a newsletter on tramadol, a press release on methadone and naloxone, and participating in the COVID-19 frequently asked questions (FAQs) of the French Society of Pharmacology and Therapeutic website (https://sfpt-fr.org/covid19). COVID-19 epidemic has been an important challenge for addictovigilance, and has proved that this monitoring is highly essential for alerting health professionals and health authorities to points of vigilance in the field of psychoactive substances.